2021
DOI: 10.1096/fj.202100664r
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of ubiquitination substrates reveals a CTLH E3 ligase complex‐dependent regulation of glycolysis

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 59 publications
(214 reference statements)
8
28
0
Order By: Relevance
“…Since the establishment of the complex as an E3 ligase, discoveries of putative or in vitro confirmed ubiquitination targets of the mammalian complex have come to light, such as transcription factor HBP1, nuclear matrix protein Lamin B2, energy regulator AMPK, glycolysis enzymes PKM2 and LDHA, and its own subunit muskelin [ 16 , 22 , 93 , 94 , 95 ]. These findings have implicated the GID/CTLH complex in a number of critical functions in different organisms, such as zygote development in D. melanogaster , nodule organogenesis in Lotus japonicus plants, organismal lifespan in Caenorhabditis elegans , neurodevelopment in X. laevis , and erythrocyte differentiation in mammals ( Figure 5 ) [ 45 , 47 , 52 , 53 , 93 , 94 , 96 , 97 , 98 ].…”
Section: Functions and Ubiquitination Targets Of The Ctlh Complex Fro...mentioning
confidence: 99%
See 2 more Smart Citations
“…Since the establishment of the complex as an E3 ligase, discoveries of putative or in vitro confirmed ubiquitination targets of the mammalian complex have come to light, such as transcription factor HBP1, nuclear matrix protein Lamin B2, energy regulator AMPK, glycolysis enzymes PKM2 and LDHA, and its own subunit muskelin [ 16 , 22 , 93 , 94 , 95 ]. These findings have implicated the GID/CTLH complex in a number of critical functions in different organisms, such as zygote development in D. melanogaster , nodule organogenesis in Lotus japonicus plants, organismal lifespan in Caenorhabditis elegans , neurodevelopment in X. laevis , and erythrocyte differentiation in mammals ( Figure 5 ) [ 45 , 47 , 52 , 53 , 93 , 94 , 96 , 97 , 98 ].…”
Section: Functions and Ubiquitination Targets Of The Ctlh Complex Fro...mentioning
confidence: 99%
“…Despite the overall conservation between the yeast and mammalian complexes, the mammalian (human or mouse) complex does not regulate gluconeogenesis, and does not ubiquitinate human Fbp1, likely because, as already mentioned, the degrons are not the same [ 16 , 134 , 135 ]. Instead, the human complex has been demonstrated to inhibit the opposite pathway, glycolysis, by regulating the ubiquitination of enzymes PKM and LDHA [ 95 ]. Instead of degradation, however, PKM and LDHA activities were increased in RanBP9-deficient cells, and global proteomic and ubiquitinome analyses suggested that non-degradative ubiquitination by the complex may be prevalent [ 95 ].…”
Section: Functions and Ubiquitination Targets Of The Ctlh Complex Fro...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the regulation of PKM2 by ubiquitination-related processes is more diverse. For instance, U-box E3 ligase CHIP reduces aerobic glycolysis by ubiquitylating and degrading PKM2 in ovarian carcinoma (OV) cells, while CTLH ubiquitylates PKM2 and lactate dehydrogenase A (LDHA) in a non-degradative pathway, thereby inhibiting glycolysis ( 19 ). On the contrary, USP7/USP20 increases the stability of PKM2 proteins by directly interacting with PKM2 ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Samples for western blots were prepared as described above, with 35 μg of protein loaded per well to 10% SDS-PAGE gels. Samples for mass spectrometry analysis for global proteomics were prepared exactly as described previously, but following the digestion and acidification, peptides were desalted using Pierce TM C18 Spin Tips (Cat# 84850)[67]. Samples were then dried in a Speed vacuum, resuspended in 0.1% formic acid, and quantified by BCA assay.…”
Section: Methodsmentioning
confidence: 99%